Comparative study of 0.5% ropivacaine and 0.5% bupivacaine for brachial plexus block by supraclavicular approach for upper limb surgeries - Modak, Shailendra; Basantwani, Shakuntala (International Journal of Basic & Clinical Pharmacology, 2017)
Background: Present study was undertaken to evaluate the clinical efficacy of 0.5% ropivacaine for supraclavicular bronchial plexus block for upper limb surgeries and comparing it with 0.5% bupivacaine in terms of characteristics of supraclavicular blockade and side effects. Methods: The design was a prospective double blind randomized study enrolling 60 patients of either sex, ASA I and II, were randomly allocated into two groups in which supraclavicular brachial plexus block was performed with nerve stimulator using 30 ml of ropivacaine 0.5% and bupivacaine 0.5% respectively. The onset and duration of sensory and motor block and possible adverse events were recorded. Results: Ropivacaine had earlier onset of sensory and motor blockade compared to bupivacaine. The duration of sensory and motor blockade was longer in group of patients treated with ropivacaine than in bupivacaine group. No statistically significant difference was found in quality of blocks in both groups. There were no adverse effects observed in the study. Conclusions: Ropivacaine 0.5% can be safely used as an alternative to bupivacaine 0.5% in supraclavicular bronchial plexus block.